Measuring the effective area and charge density of platinum electrodes for bionic devices. (15th May 2018) - Harris, Alexander R; Newbold, Carrie; Carter, Paul; Cowan, Robert; Wallace, Gordon G
Abstract: Objective . Neural stimulation is usually performed with fairly large platinum electrodes. Smaller electrodes increase the applied charge density, potentially damaging the electrode. Greater understanding of the charge injection mechanism is required for safe neural stimulation. Approach . The charge injection mechanism and charge injection capacity were measured by cyclic voltammetry. Electrodes were cleaned mechanically or by potential cycling in acidic solutions. The effective electrode area was measured by hydrogen adsorption or reduction of . Main results . The water window and safe potential window were affected by changes to electrolyte, electrode size, polishing method and oxygen concentration. Capacitance and Faradaic current contribute to the charge injection capacity. Varying voltammetric scan rate (measurement time), electrode size, polishing method, potential window, electrolyte and oxygen concentration affected the charge injection capacity and ratio of oxidation to reduction charge. Hydrogen adsorption in acidic solutions provided an inaccurate effective electrode area. Reduction of a solution phase redox species with a linear or radial diffusion profile could provide an effective electrode area. The charge density (charge injection capacity divided by electrode area) of a platinum electrode is dependent on the charge injection capacity and electrode area measurement technique. By varying cyclic voltammetric conditions, the charge density of platinum ranged from 0.15 to 5.57 mC cm −2 . Significance . The safe potential window, charge injection mechanism, charge injection capacity and charge density of platinum depends on electrolyte, size of the electrode, oxygen concentration and differences in electrode polishing method. The oxidation and reduction charge injection capacities are not equal. Careful control of a platinum electrodes surface may allow larger charge densities and safe use of smaller electrodes. New electrode materials and geometries should be tested in a consistent manner to allow comparison of potential suitability for neural stimulation.